2019
DOI: 10.1063/1.5086542
|View full text |Cite
|
Sign up to set email alerts
|

Peculiarities in breakup and transport process of shock-induced ejecta with surrounding gas

Abstract: The interaction of shock-induced ejecta with gas beyond the free surface is a critical unsolved issue and being investigated broadly. Using models containing micrometer-sized gas environments, we perform molecular dynamics simulations to investigate the coupling interactions of surrounding gases with ejecta from shock-loaded tin surface. Ejected microjets experience progressively aggravated deceleration with increasing gas density, and particle flows ahead of jet tips are suppressed. Despite the drag effect, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 67 publications
0
2
0
1
Order By: Relevance
“…强冲击作用下的金属材料动态破碎过程, 既包含 简单的单次加载微喷、层裂/微层裂破碎 [1][2][3][4][5][6][7][8][9][10][11][12][13] , 也有复 杂多次加载产生的表面微射流、主体区域反复冲击再 破碎、主体区域对微射流颗粒回收等一系列复杂过 程 [14][15][16] , 是耦合材料特性、加载状态、样品初始状态 等多因素的复杂多尺度问题, 在惯性约束核聚变、冲 击防护等领域有重要的工程价值和科学意义, 最近几 十年被广泛研究 [17][18][19] .…”
Section: 引言unclassified
“…强冲击作用下的金属材料动态破碎过程, 既包含 简单的单次加载微喷、层裂/微层裂破碎 [1][2][3][4][5][6][7][8][9][10][11][12][13] , 也有复 杂多次加载产生的表面微射流、主体区域反复冲击再 破碎、主体区域对微射流颗粒回收等一系列复杂过 程 [14][15][16] , 是耦合材料特性、加载状态、样品初始状态 等多因素的复杂多尺度问题, 在惯性约束核聚变、冲 击防护等领域有重要的工程价值和科学意义, 最近几 十年被广泛研究 [17][18][19] .…”
Section: 引言unclassified
“…On the other hand, the damage depth is closely related to the physical processes such as secondary shock and particle-gas mixing. [20][21][22] Shao et al [23] proposed an approximate description of damage depth under triangular wave loading when the material's compressibility is considered. However, under strong triangular wave loading, the effect of the relative movement is obvious and should also be taken into account when performing theoretical modeling of damage depth.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, Piriz et al [23] proposed an analytical model based on the linear Richtmyer-Meshkov instability (RMI) in solids under the conditions of high-energy-density, and showed that plasticity determined the maximum perturbation amplitude and provides simple scaling laws. Besides, molecular dynamics (MD) [1,12,24,25], Eulerian [14,26,27], and smoothed particle hydrodynamics (SPH) [28][29][30] methods have all been used to simulate the microjet formation. Dimonte et al [31] described a simple algebraic model for the microjet based on the hydrodynamics and MD simulations of the RMI.…”
Section: Introductionmentioning
confidence: 99%